Human Placental Histopathology in Preterm Stillbirth: One Center's Experience. (3rd July 2016) - Salihoğlu, Özgül; Doğan, Keziban; Sever, Nurten; Oksay, Sinem Can; Yaşar, Levent
ABSTRACT: Our aim is to identify maternal risk factors and to determine placental histopathologies in preterm stillbirths. We designed a prospective study involving a patient population ( n = 136) composed of singleton stillbirth ( n = 40) and singleton live-born neonates ( n = 96) between 23 0/7 and 36 6/7 weeks of gestation. We divided the stillbirths into groups of early ( n = 21) and late ( n = 19) stillbirths. Statistical analyses were performed using SPSS version 15 software. Small birth weight for gestational age and oligo-anhydramnios were significantly higher in the early stillbirth group ( p = 0.001, p = 0.002 respectively). Antenatal follow up was significantly lower in the late stillbirth group ( p = 0.001). Placental weight was statistically lower in the early stillbirth group ( p = 0.001). We found no significant differences in maternal vascular underperfusion, fetal vascular obstruction, inflammation and villitis of unknown etiology. Placental pathologies causing preterm labor may play an important role in the etiology of stillbirths and antenatal follow up is essential for each pregnancy.